Anti-caries effect of CPP-ACP in irradiated nasopharyngeal carcinoma patients - Sim, Christina P. C.; Wee, Joseph; Xu, Ying; Cheung, Yin-Bun; Soong, Yoke-Lim; Manton, David J. (Clinical oral investigations, 2015)
Objective The aim of this study was to determine the effect of casein phosphopeptide-amorphous calcium phosphate (CPP-ACP) on caries progression in irradiated nasopharyngeal carcinoma (NPC) patients. Methods Twenty-one males and three females (median age, 50 years) were randomized into two groups before radiotherapy. Subjects had at least eight teeth after oral health clearance. The test group used 0.4 % stannous fluoride gel and a crème containing 10 % CPP-ACP daily; the control group used a similar crème without CPP-ACP and otherwise identical care. Subjects applied the crème three times daily and fluoride gel once daily. Caries status, saliva and plaque parameters were measured pre-radiotherapy, at 2 weeks and 3 months post-radiotherapy. Results Baseline International Caries Detection and Assessment System (ICDAS) scores were 0–1126 surfaces (93.9 %), 1–28 surfaces (2.3 %), 2–40 surfaces (3.3 %) and 3–6 surfaces (0.5 %) for the control and 0–1186 surfaces (95.6 %), 1–31 surfaces (2.5 %), 2–15 surfaces (1.2 %) and 3–8 surfaces (0.7 %) for the test group. Twenty-two subjects returned at 3 months post-radiotherapy with reduced plaque pH, salivary flow, pH and buffering capacity. Nine test and 8 control subjects developed 32 and 59 new caries lesions, respectively. Test subjects showed lower caries progression than the controls: all surfaces (OR 0.51, 95 % CI 0.17∼1.59), occlusal (OR 0.20, 95 % CI 0.03∼1.29) and smooth surfaces (OR 0.61, 95 % CI 0.16∼2.38). The difference was not statistically significant. Conclusion Application of CPP-ACP did not significantly reduce caries progression in NPC patients in the first 3 months after radiotherapy as compared to controls. Clinical relevance Adjunct use of CPP-ACP with stannous fluoride gel in irradiated NPC patients gave comparable results compared to stannous fluoride gel alone in reducing caries progression.